Effects of pulp capping materials on fracture resistance of Class II composite restorations - Kucukyilmaz, Ebru; Yasa, Bilal; Akcay, Merve; Savas, Selcuk; Kavrik, Fevzi (European Journal of Dentistry, 2015)
Objective: The aim of this study was to investigate the effect of cavity design and the type of pulp capping materials on the fracture resistance of Class II composite restorations. Materials and Methods: Sixty freshly extracted, sound molar teeth were selected for the study. A dovetail cavity on the mesio-occlusal and a slot cavity on disto-occlusal surfaces of each tooth were prepared, and the teeth were divided 4 groups which one of them as a control group. The pulp capping materials (TheraCal LC, Calcimol LC, Dycal) applied on pulpo-axial wall of each cavity, and the restoration was completed with composite resin. The teeth were subjected to a compressive load in a universal mechanical testing machine. The surfaces of the tooth and restoration were examined under a stereomicroscope. The data were analyzed using factorial analysis of variance and Tukey's test. Results: For pulp capping materials, the highest fracture load (931.15 ± 203.81 N) and the lowest fracture load (832.28 ± 245.75 N) were calculated for Control and Dycal group, respectively. However, there were no statistically significant differences among all groups (P > 0.05). The fracture load of the dovetail groups was significantly higher than those of the slot cavity groups (P < 0.05). Conclusion: Dovetail cavity design shows better fracture resistance in Class II composite restorations, independent of used or not used pulp capping materials.
Keywords: Composite resins; pulp capping agents; tooth fracture